Women’s figure in the works of the exhibition of SI + SA / Mohamad Quzami An-Nuur Ahmad Radzi... [et al.] - Ahmad Radzi, Mohamad Quzami An-Nuur; Haris Fadilah, Nuraina Shuhadah; Mahmud, Nor Farizah; Ahmad Apandi, Norseha (UiTM Perak Press, 2021)
Some artist implemented women figure as their main subject matter in their artwork. Women figures carried message in different ways. However, it will be based on overall art exhibition theme. The target audience also must be studied before doing any artwork especially when working with women figure. Past research stated, past artists had manipulated women figure in their artwork. They had used women figure as main subject matter follow with supporting element and visuals. In this paper, researchers had studied past literature on implemented of women figure on the artwork and discussed the artwork for Si+Sa exhibition at Shah Alam Gallery, Selangor, Malaysia.